Perbandingan Hasil Belajar Siswa Menggunakan Media Digital Interaktif ICT dengan Media Digital Interaktif VR pada Materi Penjumlahan Pecahan Kelas V SDN Dr Soetomo V Surabaya - Amelia Putri; Dian Kusmaharti (Paedagogie, 2026)
This study aims to determine the differences in learning outcomes of fifth-grade elementary school students on the addition of fractions material between the use of interactive digital media based on Information and Communication Technology (ICT) and interactive digital media based on Virtual Reality (VR). This study was motivated by the low learning outcomes of students on the addition of fractions material and the limited use of innovative technology-based learning media that are in line with the characteristics of 21st-century learners. Interactive digital media based on ICT and VR are considered capable of helping students understand the abstract concept of fractions through visualization and learning interactions that are more interesting and meaningful. The research method used is a quantitative approach with a quasi-experimental design. The subjects of the study were fifth-grade students of Dr. Soetomo Elementary School Surabaya, who were divided into two groups: an experimental group using interactive digital media based on ICT and another experimental group using interactive digital media based on Virtual Reality (VR). Data collection techniques included learning outcome tests in the form of pretests and posttests, as well as observations to assess student responses during the learning process. The collected data were analyzed using descriptive analysis, normality tests, homogeneity tests, and independent sample t-tests. The results show that there are significant differences in learning outcomes between students who use ICT-based interactive digital media and students who use VR-based interactive digital media in learning fraction addition. Students who learn using VR-based interactive digital media achieve higher learning outcomes compared to students who use ICT-based interactive digital media. Therefore, Virtual Reality (VR)-based interactive digital media can be used as an effective alternative learning medium to improve elementary school students' mathematics learning outcomes, especially in the material of fraction addition.